2022
DOI: 10.9734/ajmah/2022/v20i130431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge, Attitude and Practice of Voluntary Blood Donation among Healthcare Support Staff of a Tertiary Health Facility in Uyo, Nigeria

Abstract: Background: Blood transfusion is a veritable intervention in many clinical situations. However, the provision of safe, readily available, affordable and adequate supply of blood and blood products is still a major public health challenge in developing countries like ours. Healthcare support staff are expected to be conversant with donor blood procurement processes and the challenges of blood supply, therefore should take the lead in forestalling the occurrence of blood supply deficits. Aims: To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…This result is in parallel to a study done in northwest Nigeria, which recorded about three-quarters (72.4%) of the respondents exhibited good knowledge of hand hygiene (Garba & Uche, 2019). The essential factor which led to this result is that healthcare workers having frequent contact with patients and their body fluids including performing clinical procedures had contribute to their good knowledge on hand hygiene (Garba & Uche, 2019). On the contrary, a study conducted in Navi Mumbai has revealed only 7.59% respondents (n=15) had good knowledge while 69.19% (n=137) was moderate in knowledge regarding hand hygiene among medical, dental and nursing students (Thakker & Jadhav, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is in parallel to a study done in northwest Nigeria, which recorded about three-quarters (72.4%) of the respondents exhibited good knowledge of hand hygiene (Garba & Uche, 2019). The essential factor which led to this result is that healthcare workers having frequent contact with patients and their body fluids including performing clinical procedures had contribute to their good knowledge on hand hygiene (Garba & Uche, 2019). On the contrary, a study conducted in Navi Mumbai has revealed only 7.59% respondents (n=15) had good knowledge while 69.19% (n=137) was moderate in knowledge regarding hand hygiene among medical, dental and nursing students (Thakker & Jadhav, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Majority of respondents (74.6%) had good knowledge of hand hygiene while 25.4% had moderate knowledge of hand hygiene. This result is in parallel to a study done in northwest Nigeria, which recorded about three-quarters (72.4%) of the respondents exhibited good knowledge of hand hygiene (Garba & Uche, 2019). The essential factor which led to this result is that healthcare workers having frequent contact with patients and their body fluids including performing clinical procedures had contribute to their good knowledge on hand hygiene (Garba & Uche, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Nkang (2002) noted that a domineering school teacher would cause the students to work harder and perform well by not giving room for indolence. However, Akpan (2003) advocated that fairness and consistency in dealing should be maintained to ensure credibility in authoritarian technique.…”
Section: Teacher's Efforts In Developing Positive Attitude In Studentsmentioning
confidence: 99%